Syndrome of Inappropriate Secretion of Antidiuretic Hormone Cholestasis and Pericardial Effusion Due to Brucellosis Infection: A Case Report - Ahmet Cumhur Dülger; Özgür Kemik; Aziz Sümer; Hüseyin Akdeniz; Mehmet Emin Küçükoğlu; Esra Turan Canbaz; Veyis Itik; Enver Aytemiz (Case Reports in Medicine)
Syndrome of inappropriate secretion of antidiuretic hormone (SIADH) is an extremely rare complication of infectious diseases. A rare case of brucellosis complicated by syndrome of inappropriate secretion of antidiuretic hormone (SIADH) cholestasis and pericardial involvement is reported. A 27-year-old woman was admitted for fever, abdominal pain, and scleral icterus. Her medical history revealed no recent use of diuretic agents. In addition to cholestasis and elevated liver enzymes, euvolemic hyponatremia, hypouricemia, low plasma osmolality, and high urinary osmolality were also detected. Surrenal and thyroid tests were also within normal range. Echocardiography revealed minimal pericardial effusion with normal cardiac functions. The final diagnosis was SIADH due to Brucellosis. Hyponatremia, cholestasis, and pericardial disease were resolved with effective antibrucellar treatment with streptomycine and doxycycline. After completing treatment of brucellosis, there was not any more evidence of cholestasis and pericardial fluid.